2015
DOI: 10.3892/mmr.2015.4570
|View full text |Cite
|
Sign up to set email alerts
|

Propofol protects against the neurotoxicity of 1-methyl-4-phenylpyridinium

Abstract: Parkinson's disease (PD) is a progressive and degenerative disorder of the central nervous system, characterized by the loss of dopaminergic neurons and muscular rigidity. Treatment with propofol (2,6‑diisopropylphenol) has been observed to attenuate oxidative stress injury via inhibition of programmed cell death. Results from the present study indicate that propofol treatment attenuates 1‑methyl‑4‑phenylpyridinium (MPP+)‑induced oxidative stress, which was demonstrated by increased levels of reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that propofol can alleviate 1-methyl-4-phenylpyridinium-induced oxidative stress by increasing the content of reactive oxygen and ATP levels, as well as by improving mitochondrial membrane potential. This prevents the neurotoxicity of 1-methyl-4-benzene pyridinium that leads to PD [ 14 ]. In general, propofol is more suitable for anesthesia in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that propofol can alleviate 1-methyl-4-phenylpyridinium-induced oxidative stress by increasing the content of reactive oxygen and ATP levels, as well as by improving mitochondrial membrane potential. This prevents the neurotoxicity of 1-methyl-4-benzene pyridinium that leads to PD [ 14 ]. In general, propofol is more suitable for anesthesia in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is a widely used intravenous anesthetic agent with the advantages of rapid metabolism, safety, controllable anesthetic state, and neuroprotective effects [8,[12][13][14]. However, its effects on STN activity and neuropsychological outcomes on asleep DBS for PD remain controversial.…”
Section: Introductionmentioning
confidence: 99%